Pengembangan Variasi Model Permainan Edukatif Berbasis DeepLearning pada Komponen Power Kebugaran Jasmani Menggunakan Flipbook Siswa Kelas VII - Solehah, Alfiyatus; Siti Nurrochmah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to produce a digital flipbook learning media product containing variations of educational games based on deep learning to improve the power component of the physical fitness of Grade VII students, which is valid and feasible to use. The research method used was Research and Development (R&D) by adopting the ADDIE development model modified into four stages (ADDE), namely Analysis, Design, Development, and Evaluation, without field implementation. Data were collected using needs analysis questionnaires (teachers and students) and evaluation sheets in the form of validation instruments from experts. The data obtained were analyzed using qualitative and quantitative descriptive analysis techniques. The results of the needs analysis showed that 71.8% of students wanted an attractive digital media display and 56.2% of students liked using a flipbook application. The product validation test results by the material expert reached 97% and by the media expert 96%, so that the average product feasibility percentage was 96.5% with very valid and very feasible criteria. Based on these results, it can be concluded that this deep learning-based educational game variation digital flipbook learning media is declared very valid and feasible to be used